Estimating Judicial Accomplishment: Applying the Legislative Accomplishment Strategy to the Decisions of the Supreme Court. (3rd July 2017) - Hendershot, Marcus E.; Liang, Ye
ABSTRACT: In order to bridge the existing divide between the landmark policy indicators of the U.S. Congress and the U.S. Supreme Court, this analysis applies the legislative accomplishment template to the Court's orally argued cases (1899 to 2004 terms). The following measurement strategy invokes an expansive array of dichotomous indicators of contemporary salience and retrospective import to create continuous-level judicial accomplishment estimates. Tests of reliability and validity for this new measure suggest that it performs well versus contemporaneous, retrospective, and network-based measures of landmark status. These new values can be utilized to better understand the institutional development of the Court as well as to discern differences within the policy-making processes of elected and life-tenured branches.